Evaluation of a randomized controlled trial on the effect on return to work with coaching combined with light therapy and pulsed electromagnetic field therapy for workers with work-related chronic stress - Karen Nieuwenhuijsen; Antonius M.C. Schoutens; Monique H.W. Frings-Dresen; Judith K. Sluiter (BMC, 2017)
Abstract Background Chronic work-related stress is quite prevalent in the working population and is in some cases accompanied by long-term sick leave. These stress complaints highly impact employees and are costly due to lost productivity and medical expenses. A new treatment platform with light therapy plus Pulsed Electro Magnetic Fields (PEMF) in combination with coaching was used to assess whether more positive effects on return to work, stress, work-related fatigue, and quality of life could be induced compared to coaching alone. Methods A placebo-controlled trial was executed after inclusion of 96 workers, aged 18-65 with work-related chronic stress complaints and who were on sick leave (either part-time or full-time). Participants were divided into three arms at random. Group 1 (n = 28) received the treatment and coaching (Intervention group), group 2 (n = 28) received the treatment with the device turned off and coaching (Placebo group) and group 3 (n = 28) received coaching only (Control group). The data were collected at baseline, and after 6, 12 and 24 weeks. The primary outcome was % return to work, and secondary outcomes were work-related fatigue (emotional exhaustion and need for recovery after work), stress (distress and hair cortisol), and quality of life (SF-36 dimensions: vitality, emotional role limitation, and social functioning). Results Eighty-four workers completed all measurements, 28 in each group. All groups improved significantly over time in the level of return to work, as well as on all secondary outcomes. No statistical differences between the three groups were found either on the primary outcome or on any of the secondary outcomes. Conclusions Light therapy with Pulsed Electro Magnetic Fields PEMF therapy has no additional effect on return to work, stress, fatigue, and quality of live compared to coaching alone. Trial registration NTR4794 , registration date: 18-sep-2014